Intervención arquitectónica en el complejo turístico de aguas termales ¨kunugyaku¨ parroquia Pilahuín - Anabel Estefania, Patiño Velastegui (2024)
The existence of 17 hot springs in the region, in provinces such as Cotopaxi, Tungurahua and Chimborazo, including the kunugyaku hot springs, constitutes a valuable resource for thermal tourism. The inhabitants of the Cunugyacu community seek to promote tourism as a means of development, through equipment that combines recreation, thermalism and nature, to attract visitors and generate economic benefits. In view of the deterioration of the facilities and poor technical planning that is present in the current state, with improvised areas that need repair, conservation or updating. The architectural intervention is proposed in the tourist complex of hot springs ´´Kunugyaku´´Pilahuín parish to improve the well-being of the tourist and offer a relaxation experience that takes advantage of the tourist and natural potential. It is proposed to use a mixed methodological approach that integrates the analysis quantitative, through surveys directed at local residents and tourists to collect data on their perceptions, expectations and qualitative analysis based on the current state of the building through the review of files that identify the internal and external characteristics of the sector. The architectural intervention process is executed according to the previously outlined strategies. It introduces a modern perspective that improves spaces for tourists. The resulting design not only addresses the identified problems, but also maximizes the potential of the place. Each proposed modification and addition is supported by detailed analysis of the information collected and reflects the creation of an environment of relaxation and well-being for the hot spring resort.